REFINEMENT OF ALUMINUM ALLOYS BY INERT GASES - A. M. Sadoha; A. T. Volochko (Литьë и металлургия)
Mechanisms of influence of inert gas on the melt for determination of ways of efficiency increase of different variants of the melt blowing are considered.